Pengujian Diskresi Pejabat Pemerintah oleh PTUN - Indah, Sentia; Frinaldi, Aldri (Lembaga Yasin AlSys, 2023)
The purpose of this research is to determine how the PTUN tests the discretion of government officials by means of normative legal research methods. So, that it could be concluded that’s discretion had Law no. 30 of 2014 regarding Government Management. Meanwhile, for discration decisions that are deemed to be violations or discrepancies announced by government bodies or officials, administrative settlement processes, administrative appeals and lawsuits can be carried out in court. Where, the use of discretion may be exercised by government officials while still exercising it for several government officials, then the testing of discretion by the PTUN against government officials is based on various specific reasons, and the discretion exercised by government officials must be accountable.